An update on vaccine therapy and other immunotherapeutic approaches for glioblastoma. (June 2013) - Reardon, David A; Wucherpfennig, Kai W; Freeman, Gordon; Wu, Catherine J; Chiocca, E Antonio; Wen, Patrick Y; Curry, William T; Mitchell, Duane A; Fecci, Peter E; Sampson, John H; Dranoff, Glenn
Outcome for glioblastoma (GBM), the most common primary CNS malignancy, remains poor. The overall survival benefit recently achieved with immunotherapeutics for melanoma and prostate cancer support evaluation of immunotherapies for other challenging cancers, including GBM. Much historical dogma depicting the CNS as immunoprivileged has been replaced by data demonstrating CNS immunocompetence and active interaction with the peripheral immune system. Several glioma antigens have been identified for potential immunotherapeutic exploitation. Active immunotherapy studies for GBM, supported by preclinical data, have focused on tumor lysate and synthetic antigen vaccination strategies. Results to date confirm consistent safety, including a lack of autoimmune reactivity; however, modest efficacy and variable immunogenicity have been observed. These findings underscore the need to optimize vaccination variables and to address challenges posed by systemic and local immunosuppression inherent to GBM tumors. Additional immunotherapy strategies are also in development for GBM. Future studies may consider combinatorial immunotherapy strategies with complimentary actions.